Pattern and severity of transverse sinus stenosis in patients with pulsatile tinnitus associated with sigmoid sinus wall anomalies. (13th July 2019) - Hewes, Daniel; Morales, Robert; Raghavan, Prashant; Eisenman, David J.
Abstract : Objective: Describe the location and severity of transverse sinus stenosis (TSS) in a consecutive series of patients with intraoperatively confirmed sigmoid sinus wall abnormalities (SSWA). Methods: A retrospective review of imaging studies from patients undergoing sinus wall reconstruction for pulsatile tinnitus associated with SSWA "was performed." Qualitative and quantitative analyses of the TSS, including the side, type, location, extent, and severity, were performed and compared with normal controls and historical controls with idiopathic intracranial hypertension (IIH). Results: Twenty‐six of 36 subjects had adequate imaging data. The majority of subjects had some degree of bilateral TSS, and the majority of stenoses involved the distal transverse sinus. Subjects with diverticulum were significantly more likely than those with dehiscence to have ipsilateral distal TSS (16 of 16 vs. 4 of 10, P = 0.009). The mean minimum transverse sinus diameter, stenosis severity grade, and overall posterior venous sinus outflow were significantly worse in the subjects as compared to normal controls ( P = 0.002), although not as severe as the comparable values in historical controls with IIH ( P < 0.003). Conclusion: Subjects with SSWA have a high incidence of TSS, with patterns differing between those with dehiscence and diverticulum. Severity of TSS and overall posterior fossa venous outflow are worse as compared to normal controls but not as severe as in subjects with IIH. These findings have implications for the pathophysiology and management of SSWA. Level of Evidence: 4 Laryngoscope, 130:1028–1033, 2020